A light-weight wear-resistant self-lubricating composite material and a preparation method thereof, and a self-lubricating sleeve

Light body wear-resistant self-lubricating composite materials are prepared through a combination of aluminum, nickel, copper, zinc, manganese and graphite, silicon and molybdenum disulfide, which solves the rust, corrosion and failure of the prior art in humid and wading environments. The wear resistance problem has achieved self-lubricating, high temperature resistance and lightweight bushing performance, and is suitable for multi-working applications in the machinery industry.

CN118957365BActive Publication Date: 2024-12-20YINGKOU GUOHONG BEARING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411445843.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-20
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Existing sintered metal oil-containing self-lubricating composite materials are prone to rust, corrosive, wear-resistant in humid and wading environments, and are costly, and oil lubrication is prone to pollution to the environment.

Method used

The light body wear-resistant self-lubricating composite materials are prepared by high-temperature sintering and hydrothermal synthesis to make self-lubricating composite materials for self-lubricating by making self-lubricating by high-temperature sintering and hydrothermal synthesis. The sleeve uses graphite, silicon and molybdenum disulfide as fillers to reduce friction and wear and provide a self-lubricating effect.

Benefits of technology

It realizes reliable self-lubricating performance in humid and wading environments, reduces material weight and cost, improves wear resistance, high temperature and rust resistance, and is suitable for use in multiple working environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the field of composite materials and preparation technology, and discloses a lightweight wear-resistant self-lubricating composite material and its preparation method, and a self-lubricating bushing. The aforementioned composite material has the following components: aluminum, nickel, copper, zinc, manganese, chromium and solid lubricant are fused in a certain proportion to obtain the composite material; wherein the mass proportion of the aluminum, nickel, zinc, manganese, chromium and solid lubricant is 30~45:10~20:1~3:0.5~1.5:0.1~1:27~31; the copper accounts for 1%~3% of the mass content of the composite material. The present invention has the advantages of self-lubrication, high temperature resistance, no corrosion, no rust, high wear resistance, good impact resistance, and can be combined with any other metal. It meets the reliable operation requirements such as rust prevention, wear resistance and lightweight in multiple working conditions such as humidity and wading, and has excellent prospects for promotion and application in the machinery industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite materials, in particular to a lightweight wear-resistant self-lubricating composite material, and also to a preparation method of the self-lubricating composite material and a self-lubricating shaft sleeve made of the self-lubricating composite material. Background Art

[0002] In the modern machinery manufacturing industry, bearing materials are a type of lubricating material with large usage and high requirements. Machines and all rotating parts need to be supported by bearings, bushings or sleeves. There are dozens of types of bearing materials used in machinery manufacturing, among which there are hundreds of casting alloy grades. The sintered metal oil-containing self-lubricating composite material is the most suitable for bearing materials with low friction, high wear resistance, and high mechanical strength requirements, and can save materials, reduce costs, and reduce the space occupied by bearings.

[0003] The mechanical strength of sintered metal oil-containing self-lubricating composite materials is higher than that of casting materials, and can even be comparable to that of structural materials. At the same time, it has good running-in, low friction coefficient, and high wear resistance. After being impregnated with oil, the sintered metal oil-containing self-lubricating composite materials can automatically adjust the lubricating oil supplied to the friction zone. The micropores contained in the material are conducive to running-in, and the lubricating oil located in the micropores can form an oil film on the surface, which can ensure boundary lubrication during startup and under various working conditions of the friction component; fine free graphite is mixed into the oil to form a high-efficiency colloidal oil graphite lubricant. In addition, fine graphite particles are embedded in the pits of the friction surface, making the oil film not easy to break, so the friction coefficient is significantly reduced, and the wear resistance is improved. However, oil lubrication is easy to pollute the environment, and the use of non-ferrous metals, most of which are copper materials, is too costly, and there are also problems such as serious damage to working parts and high replacement costs under wading and humid working conditions, easy rust, corrosion, and poor wear resistance. Therefore, it is urgent to design a self-lubricating composite material. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a lightweight, wear-resistant, self-lubricating composite material and a preparation method thereof, and a self-lubricating bushing to meet the demand for reliable self-lubrication in multiple working conditions such as moisture and wading.

[0005] A lightweight wear-resistant self-lubricating composite material, the composite material comprising the following components: aluminum, nickel, copper, zinc, manganese, chromium and a solid lubricant are fused in a certain proportion to obtain the composite material; wherein the mass ratio of the aluminum, nickel, zinc, manganese, chromium and the solid lubricant is 30-45:10-20:1-3:0.5-1.5:0.1-1:27-31; the copper accounts for 1%-3% of the mass content of the composite material.

[0006] As a further improvement of the above scheme, the particle size of the solid lubricant is 2-5 μm, and the solid lubricant includes graphite, silicon and molybdenum disulfide. The present invention uses graphite + silicon + molybdenum disulfide as fillers to lubricate the surface in relative motion from being worn or scratched, and plays a role in preventing and protecting the friction surface from damage during relative motion and reducing friction and wear.

[0007] As a further improvement of the above solution, the composition of the solid lubricant is as follows: 2wt%~5wt% graphite, 9wt%~16wt% silicon, and 9~15wt% molybdenum disulfide.

[0008] A method for preparing a self-lubricating composite material, which is used to prepare the lightweight wear-resistant self-lubricating composite material, comprises the following steps:

[0009] S1: Take graphite, silicon and molybdenum disulfide, mix and grind to obtain a solid lubricant for later use;

[0010] S2 takes aluminum, nickel, copper, zinc, manganese and chromium and performs ball milling treatment in sequence to prepare powdered materials for later use;

[0011] S3 takes solid lubricant, aluminum powder, nickel powder, copper powder, zinc powder, manganese powder and chromium powder, mixes them evenly and transfers them to a mold for compression molding to obtain a preform;

[0012] S4: After the preform is sintered at high temperature, it is cooled and demoulded to obtain a self-lubricating composite material.

[0013] As a further improvement of the above scheme, the silicon is extracted from quartz ore, and the specific operation process is as follows: silicon dioxide and carbon powder react at 1000~1400℃ to generate crude silicon, crude silicon and chlorine react at 400~500℃ to generate silicon chloride, and silicon chloride and hydrogen react at 1000~1100℃ to obtain silicon element.

[0014] As a further improvement of the above scheme, the molybdenum disulfide is prepared by a hydrothermal synthesis method, and the specific operation process is as follows:

[0015] I) adding ammonium molybdate and thiourea into deionized water to obtain a saturated solution;

[0016] II) transferring the saturated solution to a hydrothermal reactor, adding an acid catalyst, adjusting the pH of the solution to 1-3, sealing the reactor and heating it to 150-250°C, and maintaining the reaction for 10-48 hours to obtain a reaction product;

[0017] III) The reaction product is cooled, filtered, washed, and then dried to obtain molybdenum disulfide.

[0018] As a further improvement of the above scheme, during the die forming process, the pressure is 3-6 MPa and the holding time is 6-15 min. The high temperature sintering treatment is carried out in a sintering furnace at a sintering temperature of 800-1000° C. and a sintering time of 45-90 min.

[0019] A self-lubricating shaft sleeve is made from the lightweight, wear-resistant, self-lubricating composite material.

[0020] As a further improvement of the above scheme, the method for making the self-lubricating sleeve has the following specific operations:

[0021] Step 1, providing a self-lubricating composite material prepared by the preparation method;

[0022] Step 2: placing the self-lubricating composite material in a shaft sleeve mold and cold pressing to obtain a shaft sleeve.

[0023] As a further improvement of the above solution, the cold pressing is carried out in a press with a molding pressure of 60-80 MPa.

[0024] The self-lubricating composite material of the present invention is an aluminum-based composite obtained by fusing aluminum, nickel, copper, zinc, silicon, molybdenum disulfide, manganese, chromium and graphite, forming a lightweight wear-resistant system with aluminum, nickel and nickel as main components, reducing the amount of high-cost copper, and combining the lightness and wear resistance of aluminum, the high polishing and corrosion resistance of nickel, the corrosion resistance, impermeability and non-flammability of copper, the wear resistance and metallurgical bonding of zinc, manganese that can improve the hardness and strength of the material, and the high oxidation resistance and corrosion resistance of chromium. The self-lubricating composite material is coordinated to reduce the weight of the material while improving the strength, wear resistance, high temperature resistance and self-lubricating performance of the material, and is suitable for use in machinery and equipment operating on the water surface and in a humid environment.

[0025] The self-lubricating bushing made of the self-lubricating composite material of the present invention is light in weight and has good performance compared to the traditional copper bushing. It has the characteristics of self-lubrication, high temperature resistance, no corrosion, no rust, high wear resistance and good impact resistance. It can be combined with any other metal to meet the reliable operation requirements of the self-lubricating bushing such as rust prevention, wear resistance and lightweight in multiple working conditions such as humidity and wading. It has excellent prospects for promotion and application in the machinery industry. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.

[0027] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0028] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values ​​and all integers and fractions within the range.

[0029] The specific embodiments of the present invention are described in detail below.

[0030] Example 1

[0031] The present embodiment provides a lightweight, wear-resistant, self-lubricating composite material having the following components: 38 wt % aluminum, 18 wt % nickel, 1.8 wt % copper, 12 wt % zinc, 0.9 wt % manganese, 0.3 wt % chromium, 5 wt % graphite, 9 wt % silicon, and 15 wt % molybdenum disulfide.

[0032] The method for preparing the self-lubricating composite material of this embodiment comprises the following steps:

[0033] S1: Take 5wt% graphite, 9wt% silicon and 15wt% molybdenum disulfide, mix and grind to obtain a solid lubricant for later use.

[0034] The silicon is extracted from quartz ore, and the specific operation process is as follows: silicon dioxide and carbon powder react at 1000°C to generate crude silicon, crude silicon and chlorine react at 400°C to generate silicon chloride, and silicon chloride and hydrogen react at 1000°C to obtain silicon element.

[0035] The molybdenum disulfide is prepared by a hydrothermal synthesis method, and the specific operation process is as follows:

[0036] I) Add ammonium molybdate and thiourea into deionized water to obtain a saturated solution.

[0037] II) The saturated solution was transferred to a hydrothermal reactor, HCl was added to adjust the pH of the solution to 1, the reactor was sealed and heated to 150° C., and the reaction was maintained for 48 hours to obtain a reaction product.

[0038] III) The reaction product is cooled, filtered, washed with deionized water and ethanol, and then dried in a dryer at a drying temperature of 60° C. for 4 h to obtain molybdenum disulfide.

[0039] S2 takes 38wt% aluminum, 18wt% nickel, 1.8wt% copper, 12wt% zinc, 0.9wt% manganese and 0.3wt% chromium in turn and puts them into a ball mill for ball milling. The ball milling speed is 1000r / min, the ball-to-material ratio is 3:1, and the ball milling time is 4h to make a powder material for use. The particle size of the powder material is 2μm.

[0040] S3 takes solid lubricant, aluminum powder, nickel powder, copper powder, zinc powder, manganese powder and chromium powder, mixes them evenly and transfers them to a mold for compression molding to obtain a preform. During the compression molding process, the pressure is 3 MPa and the pressure holding time is 15 minutes.

[0041] S4: After the preform is subjected to high temperature sintering treatment, it is cooled and demoulded to obtain a self-lubricating composite material. The high temperature sintering treatment is carried out in a sintering furnace at a sintering temperature of 800° C. and a sintering time of 90 minutes.

[0042] Example 2

[0043] The present embodiment provides a lightweight, wear-resistant, self-lubricating composite material having the following components: 40 wt % aluminum, 15 wt % nickel, 2.2 wt % copper, 14 wt % zinc, 1 wt % manganese, 0.8 wt % chromium, 2 wt % graphite, 16 wt % silicon, and 9 wt % molybdenum disulfide.

[0044] The method for preparing the self-lubricating composite material of this embodiment comprises the following steps:

[0045] S1 Take 2wt% graphite, 16wt% silicon and 9wt% molybdenum disulfide, mix and grind to obtain a solid lubricant for later use.

[0046] The silicon is extracted from quartz ore, and the specific operation process is as follows: silicon dioxide and carbon powder react at 1200°C to generate crude silicon, crude silicon and chlorine react at 450°C to generate silicon chloride, and silicon chloride and hydrogen react at 1050°C to obtain silicon element.

[0047] The molybdenum disulfide is prepared by a hydrothermal synthesis method, and the specific operation process is as follows:

[0048] I) Add ammonium molybdate and thiourea into deionized water to obtain a saturated solution.

[0049] II) The saturated solution was transferred to a hydrothermal reactor, HCl was added to adjust the pH of the solution to 2, the reactor was sealed and heated to 200° C., and the reaction was maintained for 30 hours to obtain a reaction product.

[0050] III) The reaction product was cooled, filtered, washed with deionized water and ethanol, and then dried in a dryer at a drying temperature of 70° C. for 3.5 h to obtain molybdenum disulfide.

[0051] S2 takes 40wt% aluminum, 15wt% nickel, 2.2wt% copper, 14wt% zinc, 1wt% manganese and 0.8wt% chromium in turn and puts them into a ball mill for ball milling. The ball milling speed is 1200r / min, the ball-to-material ratio is 3:1, and the ball milling time is 3.5h to make a powder material for use. The powder material has a particle size of 5μm.

[0052] S3 takes solid lubricant, aluminum powder, nickel powder, copper powder, zinc powder, manganese powder and chromium powder, mixes them evenly and transfers them to a mold for compression molding to obtain a preform. During the compression molding process, the pressure is 4 MPa and the pressure holding time is 10 minutes.

[0053] S4: After the preform is subjected to high temperature sintering treatment, it is cooled and demoulded to obtain a self-lubricating composite material. The high temperature sintering treatment is carried out in a sintering furnace at a sintering temperature of 900° C. and a sintering time of 70 minutes.

[0054] Example 3

[0055] The present embodiment provides a lightweight, wear-resistant, self-lubricating composite material having the following components: 35wt% aluminum, 16wt% nickel, 1.6wt% copper, 15wt% zinc, 1wt% manganese, 0.4wt% chromium, 4wt% graphite, 12wt% silicon, and 15wt% molybdenum disulfide.

[0056] The method for preparing the self-lubricating composite material of this embodiment comprises the following steps:

[0057] S1: Take 4wt% graphite, 12wt% silicon and 15wt% molybdenum disulfide, mix and grind to obtain a solid lubricant for later use.

[0058] The silicon is extracted from quartz ore, and the specific operation process is as follows: silicon dioxide and carbon powder react at 1300°C to generate crude silicon, crude silicon and chlorine react at 450°C to generate silicon chloride, and silicon chloride and hydrogen react at 1050°C to obtain silicon element.

[0059] The molybdenum disulfide is prepared by a hydrothermal synthesis method, and the specific operation process is as follows:

[0060] I) Add ammonium molybdate and thiourea into deionized water to obtain a saturated solution.

[0061] II) The saturated solution was transferred to a hydrothermal reactor, HNO3 was added, and the pH of the solution was adjusted to 2. The reactor was sealed and heated to 220°C, and the reaction was maintained for 25 hours to obtain a reaction product.

[0062] III) The reaction product is cooled, filtered, washed with deionized water and ethanol, and then dried in a dryer at a drying temperature of 75° C. for 4 h to obtain molybdenum disulfide.

[0063] S2 takes 35wt% aluminum, 16wt% nickel, 1.6wt% copper, 15wt% zinc, 1wt% manganese and 0.4wt% chromium in turn and puts them into a ball mill for ball milling. The ball milling speed is 1400r / min, the ball-to-material ratio is 3:1, and the ball milling time is 3h to make a powder material for use. The particle size of the powder material is 8μm.

[0064] S3 takes solid lubricant, aluminum powder, nickel powder, copper powder, zinc powder, manganese powder and chromium powder, mixes them evenly and transfers them to a mold for compression molding to obtain a preform. During the compression molding process, the pressure is 5 MPa and the pressure holding time is 12 minutes.

[0065] S4: After the preform is subjected to high temperature sintering treatment, it is cooled and demoulded to obtain a self-lubricating composite material. The high temperature sintering treatment is carried out in a sintering furnace at a sintering temperature of 950° C. and a sintering time of 60 minutes.

[0066] Example 4

[0067] The present embodiment provides a lightweight, wear-resistant, self-lubricating composite material having the following components: 35 wt % aluminum, 14 wt % nickel, 2.1 wt % copper, 18 wt % zinc, 0.6 wt % manganese, 0.3 wt % chromium, 5 wt % graphite, 13 wt % silicon, and 12 wt % molybdenum disulfide.

[0068] The method for preparing the self-lubricating composite material of this embodiment comprises the following steps:

[0069] S1 Take 5wt% graphite, 13wt% silicon and 12wt% molybdenum disulfide, mix and grind to obtain a solid lubricant for later use.

[0070] The silicon is extracted from quartz ore, and the specific operation process is as follows: silicon dioxide and carbon powder react at 1400°C to generate crude silicon, crude silicon and chlorine react at 500°C to generate silicon chloride, and silicon chloride and hydrogen react at 1100°C to obtain silicon element.

[0071] The molybdenum disulfide is prepared by a hydrothermal synthesis method, and the specific operation process is as follows:

[0072] I) Add ammonium molybdate and thiourea into deionized water to obtain a saturated solution.

[0073] II) The saturated solution was transferred to a hydrothermal reactor, HNO3 was added, and the pH of the solution was adjusted to 3. The reactor was sealed and heated to 250°C, and the reaction was maintained for 10 hours to obtain a reaction product.

[0074] III) The reaction product is cooled, filtered, washed with deionized water and ethanol, and then dried in a dryer at a drying temperature of 80° C. for 3 h to obtain molybdenum disulfide.

[0075] S2 takes 35wt% aluminum, 14wt% nickel, 2.1wt% copper, 18wt% zinc, 0.6wt% manganese and 0.3wt% chromium in turn and puts them into a ball mill for ball milling. The ball milling speed is 1600r / min, the ball-to-material ratio is 3:1, and the ball milling time is 2h to make a powder material for use. The particle size of the powder material is 10μm.

[0076] S3 takes solid lubricant, aluminum powder, nickel powder, copper powder, zinc powder, manganese powder and chromium powder, mixes them evenly and transfers them to a mold for compression molding to obtain a preform. During the compression molding process, the pressure is 6 MPa and the pressure holding time is 6 minutes.

[0077] S4: After the preform is subjected to high temperature sintering treatment, it is cooled and demoulded to obtain a self-lubricating composite material. The high temperature sintering treatment is carried out in a sintering furnace at a sintering temperature of 1000° C. and a sintering time of 45 minutes.

[0078] Example 5

[0079] This embodiment provides a self-lubricating bushing, which is made of the lightweight, wear-resistant, self-lubricating composite material as described in any of Embodiments 1 to 4. The specific steps of the method for making the self-lubricating bushing are as follows:

[0080] Step 1, providing a self-lubricating composite material prepared by the preparation method;

[0081] Step 2: placing the self-lubricating composite material in a shaft sleeve mold, and cold-pressing the shaft sleeve in a press machine with a molding pressure of 60-80 MPa.

[0082] The following is a comparison of commercially available copper bushings and self-lubricating bushings made of the composite materials of Examples 1-4, and the weight, wear resistance, strength and high temperature resistance performance tests are carried out. The specific test process is not described here in detail. The test results are shown in Table 1.

[0083] Table 1 Performance comparison of commercially available copper bushings and self-lubricating bushings made of composite materials of Examples 1-4

[0084]

[0085] From the analysis of Table 1, it can be seen that compared with the comparative example, the self-lubricating bushings made of the composite materials of Examples 1-4 have better wear resistance, strength and high temperature resistance than the comparative example. Among them, Example 4 is the best solution. The self-lubricating bushings made of the composite materials of Example 4 weigh 0.28 times that of the comparative example, have a strength of 210% of the comparative example, have a wear resistance of 3 times that of the comparative example, and can withstand a high temperature of 380°C. The above results prove that the composite materials of the present invention are light in weight and have good performance, and can meet the reliable operation requirements of the self-lubricating bushings such as rust prevention, wear resistance and lightweight in multiple working conditions such as humidity and wading, and have excellent prospects for promotion and application in the machinery industry.

[0086] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a lightweight wear-resistant self-lubricating composite material, characterized in that: Aluminum, nickel, copper, zinc, manganese, chromium and solid lubricant are fused in a certain proportion to obtain the composite material, wherein the mass ratio of aluminum, nickel, zinc, manganese, chromium and solid lubricant is 30-45:10-20:1-3:0.5-1.5:0.1-1:27-31; copper accounts for 1%-3% of the mass content of the composite material; The particle size of the solid lubricant is 2-5 μm, and the solid lubricant is graphite, silicon and molybdenum disulfide. The composition of the solid lubricant is as follows: graphite 2wt%-5wt%, silicon 9wt%-16wt%, molybdenum disulfide 9-15wt%; The preparation method comprises the following steps: S1: Take graphite, silicon and molybdenum disulfide, mix and grind to obtain a solid lubricant for later use; S2 takes aluminum, nickel, copper, zinc, manganese and chromium and performs ball milling treatment in sequence to prepare powdered materials for later use; S3 takes solid lubricant, aluminum powder, nickel powder, copper powder, zinc powder, manganese powder and chromium powder, mixes them evenly and transfers them to a mold for compression molding to obtain a preform; S4: After the preform is sintered at high temperature, it is cooled and demoulded to obtain a self-lubricating composite material.

2. The method for preparing a lightweight wear-resistant self-lubricating composite material according to claim 1, characterized in that: The silicon is extracted from quartz ore, and the specific operation process is as follows: silicon dioxide and carbon powder react at 1000-1400°C to generate crude silicon, crude silicon and chlorine react at 400-500°C to generate silicon chloride, and silicon chloride and hydrogen react at 1000-1100°C to obtain silicon element.

3. The method for preparing a lightweight wear-resistant self-lubricating composite material according to claim 1, characterized in that: The molybdenum disulfide is prepared by a hydrothermal synthesis method, and the specific operation process is as follows: I) adding ammonium molybdate and thiourea into deionized water to obtain a saturated solution; II) transferring the saturated solution to a hydrothermal reactor, adding an acid catalyst, adjusting the pH of the solution to 1-3, sealing the reactor and heating it to 150-250°C, and maintaining the reaction for 10-48 hours to obtain a reaction product; III) The reaction product is cooled, filtered, washed, and then dried to obtain molybdenum disulfide.

4. The method for preparing the lightweight wear-resistant self-lubricating composite material according to claim 1, characterized in that: During the compression molding process, the pressure is 3-6 MPa and the holding time is 6-15 min. The high temperature sintering treatment is carried out in a sintering furnace, the sintering temperature is 800-1000° C., and the sintering time is 45-90 minutes.

5. A self-lubricating sleeve, characterized in that: The self-lubricating bushing is made of a composite material made by the preparation method according to any one of claims 1 to 4.

6. The self-lubricating sleeve according to claim 5, characterized in that: The manufacturing method of the self-lubricating sleeve is specifically performed as follows: Step 1, providing a self-lubricating composite material prepared by the preparation method according to any one of claims 1 to 4; Step 2: placing the self-lubricating composite material in a shaft sleeve mold and cold pressing to obtain a shaft sleeve.

7. The self-lubricating sleeve according to claim 6, characterized in that: The cold pressing is carried out in a press machine with a forming pressure of 60-80 MPa.